The development of Athletic Sport Management System (ASMS) using context-based information retrieval - Mustafa, Nuridawati (2008)
This study intends to develop a computerized system for athletic sport management (ASMS) that could assist administration in planning and managing the athletic sport activity.This paper proposed the used of context-based information retrieval in searching module to change the traditional key-word system.Moreover, we proposed the use of similar word detection and knowledge based in searching module to enhance the retrieval effectiveness. This paper will discuss the early stages of the development phase which is mainly about context-based information retrieval and present the proposed system architecture for the system.